Analysis of Determinants of Type 2 Diabetes Mellitus: A Literature Review - Adzkiya Safitri; Yuanita Windusari; Iche Andriyani Liberty (GLOBAL HEALTH SCIENCE GROUP, 2026)
Type 2 Diabetes Mellitus (T2DM) is a global health issue, with 537 million cases reported in 2021 and projected to increase to 783 million by 2045. Indonesia ranks fifth globally, with T2DM prevalence rising to 8.5% in 2018. The high number of cases and the risk of severe complications, such as heart disease, stroke, and kidney failure, underline the need for an in-depth study of risk factors to mitigate the disease's impact. Objective to further examine the determinants of Type 2 Diabetes Mellitus. This study employed a literature review approach using search engines such as Google Scholar, PubMed, ScienceDirect, and BMC with the keywords